The Handbook of Manufacturing Engineering ~ Factory Operations: Planning and INstructional Methods - CROWSON, Richard, WALKER, Jack (Taylor & Francis, 2006)
The Handbook of Manufacturing Engineering ~ Factory Operations: Planning and INstructional Methods